Local predictive optimization of globally planned motions for truck-trailer systems - Dahlmann, Julian; Völz, Andreas; Lukassek, Markus; Graichen, Knut (IEEE Transactions on Control Systems Technology, 2024)

Model predictive control for agricultural machines with implements - Lukassek, Markus; Völz, Andreas; Szabo, Tomas; Graichen, Knut (Proceedings 28th Mediterranean Conference on Control and Automation (MED), 2020)

Model predictive path-following control for general n-trailer systems with an arbitrary guidance point - Lukassek, Markus; Völz, Andreas; Szabo, Tomas; Graichen, Knut (Proceedings European Control Conference (ECC 2021), 2021)

Model predictive path-following control for truck–trailer systems with specific guidance points - Design and experimental validation - Lukassek, Markus; Dahlmann, Julian; Völz, Andreas; Graichen, Knut (Mechatronics, 2024)
This article presents an experimental validation of a model predictive path-following control algorithm (PF-MPC ) applied to a truck–trailer system, encompassing both forward and backward motions. The proposed controller is designed to precisely follow a predefined path generated by a path planner, with a designated guidance point positioned on either the truck or the trailer. The algorithm’s performance is assessed through implementation and validation on a model-scaled truck–trailer system, where MPC, state estimation, and low-level control are executed on a microcontroller (MCU ). The experimental results demonstrate the effectiveness of the proposed control approach in achieving highly accurate path-following performance, even when operating in the challenging context of unstable backward motion, and with the involvement of up to two trailers. Moreover, the successful implementation of the algorithm on a microcontroller underscores its suitability for real-time control applications. The results of this study collectively highlight the promising potential of the proposed control algorithm for practical utilization in autonomous driving systems.<br
Keywords: Model predictive control; Path-following control; Vehicle state estimation; Truck–trailer systems; Automotive; Microcontroller